The Influence of the Index Card Match Type Cooperative Learning Model on the Learning Outcomes of Vocational High School Students - Harahap, Siti Maulidinah; Wijaya, Kinanti; Izzadati, Zhili; Atika, Liana; Rani, Cut Meuthia (MANDAILING GLOBAL EDUKASIA, 2024)
This research aims to determine the effect of the Index Card Match Type Cooperative Learning Model on the Learning Outcomes of DPIB Basic Principles at State Vocational School 1 Percut Sei Tuan. This research method is a Quasi-Experimental design. This method is used to measure variables before and after to see the causal relationship of the phenomenon under study. Based on the research results, the use of the Index Card Match Type Cooperative Learning Model has a better impact on learning outcomes in the cognitive domain of DPIB Basic Principles on Building Statics elements. This is proven by research results which show that the average cognitive learning outcomes of students who were taught using the Index Card Match Type Cooperative Learning Model was 73.06, higher than the average learning outcomes of students who were treated with the Direct Instruction model, namely amounting to 61.94. This is also reflected in the research data, the t test results show a t value of 3.73 compared to the t table value of 1.670 (t value > t table). Based on these differences, both theoretically and proven by statistical analysis carried out in this research, it can be concluded that the Index Card Match Type Cooperative Learning Model has a significantly different influence on student learning outcomes on DPIB Basic Principles in Building Statics Elements for class students X DPIB Skills Program State Vocational High School 1 Percut Sei Tuan.